TINGKAT PENGETAHUAN SISWA SD BINA PUTRA SURABAYA TENTANG MAJALAH DINDING SEKOLAH - Sari, Yustisia Ditya; Swestin, Grace (Scriptura, 2014)
The purpose of this research is to delve into the level of knowledge or cognitive response of students at Bina Putra Elementary School Surabaya on the function, nature, and format of their wall magazine as the school’s communication media. Due to various limitations in the access to information experienced by the students, wall magazine becomes the simplest and most practical means of delivering information about the values and activities in the organization. That is why knowledge of information in the wall magazine becomes significant. This research utilizes Stimulus-Organism-Response (S-O-R) theory and surveyed students in the 4th to 6th grade who are both audience and producers of the wall magazine content. The descriptive analysis reveals that the students have a high level of knowledge on the information posted. This implies that the wall magazine is able to serve as a communication medium for the students. However, the findings also suggest that students’ knowledge is relatively lower on aspects ofnewness and factuality of information as well as news and articles on events happening around the school. The result shows that the journalistic aspect of the wall magazine needs to be improved.